Peran akhlak dalam membangun peradaban islam yang berkemajuan - Firmansyah, Aditya (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of morality (akhlaq) in building a progressive Islamic civilization in the midst of modern challenges. The method used is library research with a descriptive-analytical approach based on relevant literature. The findings indicate that morality plays a strategic role in shaping individual character, maintaining social stability, and promoting sustainable civilization development. At the individual level, morality serves as the foundation for building a balanced personality in spiritual, emotional, and intellectual aspects. At the social level, morality becomes the main pillar in creating a harmonious, just, and civilized society. Meanwhile, in the context of civilization, morality contributes to the integration of ethical values with the development of science, leadership, and responses to globalization challenges. Therefore, strengthening and revitalizing moral values through education and social environments are essential steps toward achieving a progressive and sustainable Islamic civilization.